The impact of total body irradiation on the outcome of patients with follicular lymphoma treated with autologous stem-cell transplantation in the modern era: a retrospective study of the EBMT Lymphoma Working Party - El-Najjar, Inas; Boumendil, A.; Luan, J. J.; Bouabdallah, R.; Thomson, K.; Mohty, M.; Colombat, P.; Biron, P.; Tilly, H.; Pfreundschuh, M.; Cordonnier, C.; Sureda, A.; et al. (Annals of oncology, 2014)
BACKGROUND: The aim of this study was to investigate the impact of the high-dose regimen on the outcome of patients with follicular lymphoma (FL) having had autologous stem-cell transplantation (ASCT) in a recent time period. - PATIENTS: Between 1995 and 2007, 2233 patients with FL had their first ASCT with either a total body irradiation (TBI)-containing regimen or carmustin, etoposide, cytarabine and melphalan (BEAM), of which 47% were autografted in first remission. - RESULTS: After a median observation time of 73 months (interquartile range 30-107), 5- and 10-year non-relapse mortality (NRM) was similar (6% and 10% in both groups). No significant NRM differences became evident after multivariate adjustment for confounders. Secondary malignancies were observed in 9.7% and 7.9% of the patients after TBI and BEAM (P = 0.19), which were treatment-related myelodysplastic syndromes/acute myelogenous leukaemia (t-MDS/AML) in 3.4% and 2.8% (P = 0.57). The median time to t-MDS/AML was around 50 months in both groups. Because of a lower relapse incidence, TBI was associated with better event-free survival reaching statistical significance in the patients transplanted in first remission but not in those transplanted beyond first remission. - CONCLUSIONS: In patients with FL who received TBI-based ASCT after 1995 increased NRM and t-MDS/AML risks did not emerge compared with BEAM while disease control was at least equivalent.